2016
DOI: 10.1016/j.sleep.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration and breast cancer risk among black and white women

Abstract: Background Sleep has been suggested to influence breast cancer risk, however the evidence is mixed. Black women have higher prevalence of both short (<6 hr) and long (≥9 hr) sleep duration and are more likely to develop more aggressive, hormone receptor negative breast cancer. No study has examined the relationship between sleep and breast cancer in blacks. We focused on race-specific associations among the blacks. Methods In the Southern Community Cohort Study (SCCS), a prospective study of which 2/3 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 26 publications
3
39
3
Order By: Relevance
“…Finally, we illustrated that sleep duration <6 hour/day was insignificant risk factor for FBC (OR=1.26). It shown that short sleep duration might be a risk factor for hormone receptor-negative FBC [66]. The present study illustrated that high consumption of fat rich foods represented a significant risk factor for FBC (OR=2.48).…”
Section: /12supporting
confidence: 58%
See 1 more Smart Citation
“…Finally, we illustrated that sleep duration <6 hour/day was insignificant risk factor for FBC (OR=1.26). It shown that short sleep duration might be a risk factor for hormone receptor-negative FBC [66]. The present study illustrated that high consumption of fat rich foods represented a significant risk factor for FBC (OR=2.48).…”
Section: /12supporting
confidence: 58%
“…Further, it is expected that the cumulative incidence of FBC in the developed areas would be lowered by more than one half, from 6.3% to 2.7% by age 70, if females had the mean number of births and lifetime duration of breast-feeding that have been found in the developing areas till recently. Breast-feeding could account for almost 66.0% of the expected lowered in FBC incidence [10]. Trends in lifestyle factors vary greatly between different settings.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep loss increases susceptibility to the common cold [21], alters gene expression [22], and affects metabolism [23]. Moreover, in epidemiological studies, sleep disturbances are associated with cardiovascular conditions [24], cancer [25], Type II diabetes [26], and Alzheimer’s disease [27]. Because these conditions are more prevalent with advancing age, sleep alterations might explain many deleterious effects generally attributed to aging (hereafter, the preserved-sleep-need view).…”
Section: Theories Of Whether Older Adults Need Sleepmentioning
confidence: 99%
“…Particularly, African Americans have a higher rates of both long (>9 hours) and short sleep (<5 hours) compared to whites [12]. A recent study showed that black women with shorter sleep duration had a higher risk of ER-negative and PR-negative breast cancer [13]. Also, the higher incidence of aggressive breast tumors in African Americans and the potential for varying risk factors according to tumor type drives the current study.…”
Section: Introductionmentioning
confidence: 95%